Sociodemographic profile of blind people: associations with knowledge, attitude and practice about sexually transmitted infections - Andressa Kaline Ferreira Araújo; Inacia Sátiro Xavier de França; Alexsandro Silva Coura; Sérgio Ribeiro dos Santos; Ana Paula Andrade Ramos; Lorita Marlena Freitag Pagliuca (Rev Rene)
Objective: to analyze associations among sociodemographic characteristics and knowledge, attitude and practice ofblind people about sexually transmitted infections. Methods: descriptive transversal study with a quantitative approach.Participants were 36 blind individuals. The questionnaire Knowledge, attitude and practice about sexually transmittedinfections was used. Absolute and relative frequencies were calculated. There were Chi-square test and chi-square Exact.Results: most participants are elderly, unmarried, with elementary school and not working. Knowledge, attitude andpractice about sexually transmitted infections are inadequate (p<0.05). Religion (p<0.001), work (p<0.001), not workingreason (p<0.001) and education (p=0.003) had associations with the attitude about sexually transmitted infections. Gender(p<0.001), marital status (p=0.019) and education (p=0.020) had associations with practice. There was no associationbetween sociodemographic characteristics and knowledge. Conclusion: sociodemographic characteristics may interferewith the attitude and practice of blind people about sexually transmitted infections, and the nurse should consider thesecharacteristics in professional practice with those subjects.